Effects of Trigger Point Dry Needling on Strength Measurements and Activation Levels of the Gluteus Medius: A Quasi-Experimental Randomized Control Study - Eric Schneider; Elizabeth S. Moore; Rob Stanborough; Emily Slaven (International Journal of Sports Physical Therapy)
# Background